Peningkatan Konektifitas Service VPLS Redundant Path Dengan Rapid Spanning Tree Protocol - Fikri Iqromuddin; Novi Dian Nathasia; Iskandar Fitri (Universitas Widyagama Malang, 2017)
Virtual Private LAN Service is already very popular among the enterprise industry which is a point to point network or multipoint to multipoint l2VPN service, VPLS provides transparent bridge between customers connected to geographically dispersed locations delivered via MPLS backbone by utilizing features such as MPLS Fast reroute and traffic engineering. Redundant paths can be applied to the VPLS service on the access side and backbone to maintain link performance that aims to minimize down time during network fails on the VPLS service. In this research, the implementation of redundant path using RSTP to prevent forwarding loop switching network in VPLS service to protect end-to-end data traffic with VPLS mesh-pseudowire and spoke-pesudowire with RSTP is the most optimal result compared to STP and build reliable network System with high performance for use in modern industry.